ASINXRON DVIGATEL- TIRISTORLI KUCHLANISH ROSTLAGICHI TKR-AD TEZLIGINI ROSTLASH TIZIMI TAHLIL QILISH. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation. A speed control system based on an asynchronous motor (AC motor) and a thyristor voltage regulator (Thyristor Voltage Regulator, TKR-AD) is a widely used technology in industry and transportation. Asynchronous motors are known for their simplicity, reliability and low cost, making their use in speed control systems efficient and economical.